2000
DOI: 10.1046/j.1524-4725.2000.0260111029.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Glycosaminoglycans Production in Sclerosing Basal Cell Carcinoma-Derived Fibroblasts and Stimulation of Normal Skin Fibroblast Glycosaminoglycans Production by a Cytokine-Derived from Sclerosing Basal Cell Carcinoma

Abstract: Sclerosing basal cell carcinoma (S-BCC) is characterized by an abundant stroma. There is evidence that some tumor cells secrete cytokines that are mitogenic for stromal fibroblasts (FBs). From this study we report increased glycosaminoglycan (GAG) production by cultures of S-BCC FBs in comparison to cultures of nodular BCC (N-BCC) FBs and normal skin FBs. GAG production was measured by cetylpyridinium chloride precipitation of incorporated [3H]-glucosamine. The sclerosing BCC FBs demonstrated a significant inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The clinical appearance of our patient's lesion resembled the skin dimpling or retraction that can be seen overlying some breast cancers and to some extent mimics the appearance of a pursestring wound closure. Sclerosing BCC tumor cells have been shown to secrete cytokines, such as transforming growth factor beta, that promote proliferation of fibroblasts and production of glycosaminoglycans . Aggressive BCC tumor cell subtypes have high expression of a variety of collagenases and matrix metalloproteinases, which facilitate tumor invasion and spread through the dermis .…”
Section: Discussionmentioning
confidence: 99%
“…The clinical appearance of our patient's lesion resembled the skin dimpling or retraction that can be seen overlying some breast cancers and to some extent mimics the appearance of a pursestring wound closure. Sclerosing BCC tumor cells have been shown to secrete cytokines, such as transforming growth factor beta, that promote proliferation of fibroblasts and production of glycosaminoglycans . Aggressive BCC tumor cell subtypes have high expression of a variety of collagenases and matrix metalloproteinases, which facilitate tumor invasion and spread through the dermis .…”
Section: Discussionmentioning
confidence: 99%
“…48 Furthermore, Moy et al, demonstrated that fibroblasts from nodular and sclerosing BCC, produce more GAGs, when compared with normal fibroblasts. 49 The authors suggested that cells from superficial and nodular BCC types are capable of producing cytokines which alter stromal fibroblast production of GAGs and stimulate collagenase synthesis. 49 In addition, Bertheim et al, demonstrated that in nodular BCC, HA staining of the tumour strands was weak to moderate, denoting increased proliferative activity.…”
Section: Discussionmentioning
confidence: 99%
“…49 The authors suggested that cells from superficial and nodular BCC types are capable of producing cytokines which alter stromal fibroblast production of GAGs and stimulate collagenase synthesis. 49 In addition, Bertheim et al, demonstrated that in nodular BCC, HA staining of the tumour strands was weak to moderate, denoting increased proliferative activity. They also reported that the differentiated surrounding tumour stroma stained strongly for HA.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Further clinical and experimental evaluation may elucidate the sclerosing mechanism, although the causative factor may differ in each malignancy. On the other hand, the resultant stroma formation can have impacts on mitogenic and motogenic activities of tumour cells.…”
Section: A Case Of Syringoid Eccrine Carcinoma With Circumscribed Abumentioning
confidence: 99%
“…1 EAC was first described by Darrier. 2 Subsequently, Ackerman, basing on the histopathologic aspects, distinguished between superficial and deep forms. 3 Some authors considered EAC as a hypersensitivity reaction that may be associated with underlying diseases.…”
Section: Erythema Annulare Centrifugum As the Presenting Sign Of Breamentioning
confidence: 99%